2008
DOI: 10.1016/j.virol.2008.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of restricted CD4 T cell expansions in SIV-infected macaques resistant to SHIV89.6P superinfection

Abstract: Attempts to evaluate the protective effect of live attenuated SIV vaccine strains have yielded variable results depending on the route of immunization, the level of attenuation, the level of divergence between the vaccine candidate and the challenge. The protective mechanisms induced by these vaccines are still not well understood. In an effort to address whether the diversity of the CD4+ T cell repertoire in cynomolgus macaques plays a role in the immunological protection following SIVmacC8 infection, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…In addition, cerebral tissues were harvested from feline immunodeficiency virus-infected cats (12 weeks old) [44] and RAG1 −/− mice (>52 weeks of age) [47], housed under SPF conditions, from which RNA was prepared as described above. Brain tissues from simian (SIV; n = 10) [48] or simian-human immunodeficiency virus-infected (SHIV; n = 3) [49] or FIV-challenged adult cynomolgus macaques (n = 2) [50] were analyzed by initial preparation of RNA followed by RT-PCR amplification of cDNA and sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cerebral tissues were harvested from feline immunodeficiency virus-infected cats (12 weeks old) [44] and RAG1 −/− mice (>52 weeks of age) [47], housed under SPF conditions, from which RNA was prepared as described above. Brain tissues from simian (SIV; n = 10) [48] or simian-human immunodeficiency virus-infected (SHIV; n = 3) [49] or FIV-challenged adult cynomolgus macaques (n = 2) [50] were analyzed by initial preparation of RNA followed by RT-PCR amplification of cDNA and sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…A correlation between susceptibility to superinfection and T cells from peripheral blood, however, was not observed in their study. In contrast, Salha et al observed that the diversity of the CD4 + T-cell repertoire did play a role in SIV-infected macaques resistant to simian-human immunodeficiency virus (SHIV)89.6P superinfection [14]. Furthermore, Pahar et al later demonstrated that primary infection of macaques with SHIV SF162P3 conferred partial to complete protection against subsequent challenge with the highly pathogenic SIVmac251 and suggested that the preservation of intestinal CD4 + memory T cells might be associated with protection from challenge [15].…”
Section: Introductionmentioning
confidence: 94%
“…SIV mac C8-and SIV mac J5-vaccinated animals showed protection against SHIV-89.6 with lower CD4 + repertoire and dominant CD4 + T cells [97]. Two versions (NM-3 or NM-3n) of the parental SHIV NM-3rN strain were used as vaccines and animals challenged with SHIV NM-3rN live virus showed protection against NM-3rN [98].…”
Section: Protection Against Shiv Chimaerasmentioning
confidence: 99%